Analysis of the Potential Economic Sectors on Poverty in Malang District and Madiun District - Lailatul Isti’adah; Wiwin Priana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Development is an ongoing process embraced by nearly all nations globally, as it constitutes an integral aspect of a nation's pursuit of progress. The objectives of this research are delineated as follows: Firstly, to identify the fundamental sectors in Madiun Regency and Malang Regency. Secondly, to ascertain the sectors propelling growth in other regions within Madiun Regency and Malang Regency. Thirdly, to discern which sectors are experiencing accelerated growth rates in both regions. Fourthly, to determine sectors exhibiting specialization or locational advantages in Madiun Regency and Malang Regency. Lastly, to classify the economic growth within Madiun Regency and Malang Regency. Employing a descriptive-quantitative analysis method, this research provides an overview or description of the variables associated with the phenomenon under study. The findings of this research demonstrate a significant influence of the Basic Sector on poverty levels. Additionally, the coefficient of determination value, at 65.7%, corroborates the contribution of independent variables in elucidating variations in poverty levels.